HUBUNGAN RELIGIUSITAS DAN KEPRIBADIAN TERHADAP PERILAKU PROSOSIAL PADA PERAWAT - Danang Satrio; Arif Budiharjo; Dyah Prasetyani (LPPM Universitas Pekalongan, 2020)
One of the professions that plays an important role in maintaining the quality of health services is nursing because nurses as the spearhead of service in the hospital always interact with patients in which there is a reciprocal relationship between individuals so that prosocial behavior appears. Religiosity and personality together can be used as predictors to predict prosocial behavior in nurses. This study aims to determine the relationship between religiosity and personality towards prosocial behavior. This research uses descriptive research with a quantitative approach. intended to get an overview and information about the Qolbu Insan Mulia Hospital (QIM) Batang Regency.